Reliability Enhancement of Power IGBTs under Short-Circuit Fault Condition Using Short-Circuit Current Limiting-Based Technique - Mohsenzade, Sadegh; Naghibi, Javad; Mehran, Kamyar (Energies (Basel), 2021)
Like the widely-used semiconductor switch, Insulated Gate Bipolar Transistors (IGBTs) are subject to many failures and degradation in power electronic converters. In Short Circuit Fault (SCF), as the most reported failures in IGBTs, drastic, sudden temperature rise, and peak SCF current are widespread failures owing to a relatively long delay of the protection subsystem. This paper proposes a protection strategy to limit the junction temperature rise by limiting the SCF current by adding a small value resistor in the IGBT emitter. Second, it reduces the SCF current to a value much less than the saturated current. With the proposed control approach, sudden temperature rise during SCF is controlled, preventing significant failure in IGBTs. The extension of the permissible SCF time is achieved even for the cases with temporary arcs. A simple control loop activates in the SCF condition and does not create slow transients for the IGBT. The results of this paper are validated through simulation and experiment.